Effects of the Mediterranean Diet during pregnancy on the onset of allergy in at risk children: A study protocol of a multi-center, randomized- controlled, parallel groups, prospective trial (the PREMEDI study) - Coppola, Serena; Paparo, Lorella; Chiariotti, Lorenzo; Ercolini, Danilo; Nocerino, Rita; de Giovanni di Santa Severina, Anna Fiorenza; Carucci, Laura; De Filippis, Francesca; Agangi, Annalisa; Napolitano, Marcello; Passariello, Annalisa; Messina, Francesco; et al. (Frontiers in Nutrition, 2022)
Introduction: Maternal diet during pregnancy has been linked to offspring allergy risk and it could represent a potential target for allergy prevention. The Mediterranean Diet (MD) is considered one of the healthiest dietary models. Randomized-controlled trials on the effect of MD in preventing pediatric allergic diseases are still needed. Methods and Analysis: The Mediterranean Diet during Pregnancy study (PREMEDI) will be a 9-month multi-center, randomized-controlled, parallel groups, prospective trial. Healthy women (20-35 years) at their first trimester of pregnancy of at risk for atopy baby, will be randomly allocated to Group 1 (standard obstetrical and gynecological follow-up and nutritional counseling to promote MD) or Group 2 (standard obstetrical and gynecological follow-up alone). 138 mother-child pair per group will be needed to detect a reduction in cumulative incidence of ≥ 1 allergic disease at 24 months of age. The primary study aim will be the evaluation of the occurrence of allergic disorders in the first 24 months of life. The secondary aims will be the evaluation of maternal weight gain, pregnancy/perinatal complications, growth indices and occurrence of other chronic disorders, mother-child pair adherence to MD and gut microbiome features, breastfeeding duration and breast milk composition, epigenetic modulation of genes involved in immune system and metabolic pathways in the offspring. Ethics and Dissemination: The study protocol has been approved by the Ethics Committee of the University of Naples Federico II (number 283/21) and it will be conducted in accordance with the Helsinki Declaration (Fortaleza revision, 2013), the Good Clinical Practice Standards (CPMP/ICH/135/95), the Italian Decree-Law 196/2003 regarding personal data and the European regulations on this subject. The study has been registered in the Clinical Trials Protocol Registration System http://clinicaltrials.gov: NCT05119868.